# Prove that $\sinh(\cosh(x)) \geq \cosh(\sinh(x))$

Prove that

$$\sinh(\cosh(x)) \geq \cosh(\sinh(x))$$

I tried to tackle this problem by integrating both lhs and rhs, in order to get two functions who show clearly that inequality holds. I've struggled for this problem a little bit, i don't know if there's any trick that can help. Maybe knowing that

$$\cosh^{-1}(x) = \pm \ln\left(x + \sqrt{x^2 - 1}\right)$$

Can help?

• Jensen is useful only when we have a function and a constant, not with composite functions... Even if I think there are some similarities... Commented May 26, 2015 at 18:11
• cheers for teaching me something new :). Commented May 26, 2015 at 18:12
• Physics guy here. I don't have any idea how to do math proofs, but isn't it true that a "small function" acting on a "big function" is always larger than the alternative? Since cosh(x)>sinh(x) for all x, this is a no brainer, right? This is how I remember e^pi>pi^e. Anyway, I've never spoken on Math.SE and generally run in fear from mathematicians, so please, let me down gently! Commented May 27, 2015 at 4:03
• @user1717828 $\ln x$ is smaller than $x^2$, but $\ln (x^2) = 2\ln x$ is smaller than $(\ln x)^2$.
– user21467
Commented May 27, 2015 at 4:21
• @StevenTaschuk, aaaaannnnnddd this is why our field would crumble without mathematicians keeping us in check. Thanks! Commented May 27, 2015 at 4:43

Here's a solution with very little calculus. First, an identity: \begin{align*} \sinh^2(a+b) - \sinh^2(a-b) &= (\sinh a\cosh b + \cosh a\sinh b)^2 - (\sinh a\cosh b - \cosh a\sinh b)^2 \\ &= 4\sinh a \cosh a\sinh b \cosh b \\ &= \sinh(2a)\sinh(2b) \end{align*} Taking $a=e^x/2$ and $b=e^{-x}/2$, we get \begin{align*} \sinh^2(\cosh x) - \sinh^2(\sinh x) &= \sinh(e^x) \sinh(e^{-x}) \\ &\ge e^xe^{-x} &&\text{(since $\sinh t\ge t$ for $t\ge 0$)} \\ &= 1 \\ &= \cosh^2(\sinh x) - \sinh^2(\sinh x) \end{align*} Cancelling $\sinh^2(\sinh x)$ and taking square roots gives the desired inequality.

Calculus is needed here only to justify the inequality $\sinh t\ge t$ (for $t\ge 0$).

Update: Another nice thing about this method is that it points the way to a more exact inequality. It turns out that $$\sinh u\sinh v \ge \sinh^2\sqrt{uv}$$ for $u,v\ge 0$. (Proof 1: $\frac12(u^{2m+1}v^{2n+1} + v^{2m+1}u^{2n+1})\ge (uv)^{m+n+1}$ by AM/GM; divide by $(2m+1)!\,(2n+1)!$ and apply $\sum_{m=0}^\infty \sum_{n=0}^\infty$. Proof 2: Check that $t\mapsto\ln\sinh(e^t)$ is convex (for all $t$) by computing its second derivative.)

Applying this with $u=e^x$ and $v=e^{-x}$ above, we get $$\sinh^2(\cosh x) \ge \cosh^2(\sinh x) + \underbrace{\sinh^2(1) - 1}_{\approx 0.3811}$$ with equality when $x=0$.

• (+1) Very nice. Since $\cosh(x)\gt0$, we don't need to worry about signs when taking square roots.
– robjohn
Commented May 27, 2015 at 4:22

For any $y \ge 0$, notice

$$e^y - 1 = \int_0^y e^x dx \ge \int_0^y (1+x) dx \ge \int_0^y \left(1+\frac{x} {\sqrt{1+x^2}}\right)dx = y + \sqrt{1+y^2} - 1$$ we have this little inequality: $$\sqrt{1+y^2} - y = \frac{1}{\sqrt{1+y^2} + y} \ge e^{-y}$$

Using MVT, we can find a $\xi \in (y,\sqrt{1+y^2})$ such that

$$\sinh\sqrt{1+y^2} - \sinh(y) = \cosh(\xi)\left(\sqrt{1+y^2} - y\right) \ge \cosh(\xi) e^{-y} \ge e^{-y}$$

Since $e^{-y} = \cosh(y) - \sinh(y)$, this leads to $$\sinh\sqrt{1+y^2} \ge \cosh(y)\\$$

Substitute $y$ by $\sinh(x)$ and notice $\sqrt{1+y^2} = \cosh(x)$, this reduces to our desired inequality:

$$\sinh(\cosh(x)) \ge \cosh(\sinh(x))$$

Let $t=\sinh x$. Now we can square the inequality and instead try proving $$\sinh^2(\sqrt{1+t^2})=\sinh^2(\cosh x) \ge \cosh^2(\sinh x)=1+\sinh^2t$$

So it is enough to show $f(t) = \sinh^2(\sqrt{1+t^2})-\sinh^2t-1 \ge 0$. As $f$ is even and $f(0)> 0$, it is enough to show it is increasing for positive $t$. Hence we look at $$f'(t) = \frac{t\sinh (2\sqrt{1+t^2})}{\sqrt{1+t^2}} - \sinh(2t)$$ To show this is positive, it suffices to note by differentiating that the function $g(t) = \dfrac{\sinh t}{t}$ is increasing, so $g(2\sqrt{1+t^2})> g(2t)$. Hence proved...

For $x\ge0$, the Mean Value Theorem says that for some $\sinh(x)\lt\xi\lt\cosh(x)$, \begin{align} \sinh(\cosh(x))-\sinh(\sinh(x)) &=\cosh(\xi)(\cosh(x)-\sinh(x))\\ &\gt\cosh(\sinh(x))\,e^{-x}\tag{1} \end{align} Furthermore, $$\cosh(\sinh(x))-\sinh(\sinh(x))=e^{-\sinh(x)}\tag{2}$$ Therefore, subtracting $(2)$ from $(1)$, then applying $\cosh(x)\ge1$ and $\sinh(x)\ge x$, we get \begin{align} \sinh(\cosh(x))-\cosh(\sinh(x)) &\gt e^{-x}\cosh(\sinh(x))-e^{-\sinh(x)}\\ &\ge e^{-x}-e^{-\sinh(x)}\\ &\ge0\tag{3} \end{align} Since $\sinh(\cosh(x))-\cosh(\sinh(x))$ is even, $(3)$ implies that strict inequality holds for all $x$: $$\sinh(\cosh(x))\gt\cosh(\sinh(x))\tag{4}$$

Substitute :

$$e^y=x$$

We get :

$$\sinh\left(\frac{\left(x+\frac{1}{x}\right)}{2}\right)\geq \cosh\left(\left(x-\frac{1}{x}\right)\cdot0.5\right)$$

Now substitute again we get :

$$\left(x+\frac{1}{x}\right)0.5-\frac{1}{\left(\left(x+\frac{1}{x}\right)\cdot0.5\right)}-\left(\left(x-\frac{1}{x}\right)0.5+\frac{1}{\left(x-\frac{1}{x}\right)0.5}\right)\geq 0$$

Or :

$$\frac{\left(3x^{4}+1\right)}{\left(1-x\right)x\left(x+1\right)\left(x^{2}+1\right)}\geq0$$

The conclusion is smooth .

• Oups .I forgot to say it use complex number...Make a comment if you see something else Commented Jun 12, 2021 at 13:28

We can actually prove strict inequality.

Let's start with the observation that, since $$\cosh u\ge1\gt0$$ for all $$u$$ and $$\sinh u\gt u\gt0$$ for all $$u\gt0$$, we have

\begin{align} \sinh(\cosh x)\gt\cosh(\sinh x) &\iff\sinh^2(\cosh x)\gt\cosh^2(\sinh x)\\ &\iff\cosh^2(\cosh x)-1\gt\cosh^2(\sinh x)\\ &\iff\cosh^2(\cosh x)-\cosh^2(\sinh x)\gt1\\ &\iff(\cosh(\cosh x)+\cosh(\sinh x))(\cosh(\cosh x)-\cosh(\sinh x))\gt1 \end{align}

Now $$\cosh(\cosh x)+\cosh(\sinh x)\ge1+1=2$$, so it suffices to prove that

$$\cosh(\cosh x)-\cosh(\sinh x)\gt{1\over2}$$

But $$\cosh(a+b)-\cosh(a-b)=2\sinh a\sinh b\gt2ab$$ (with the inequality requiring $$a,b\gt0$$), we have, letting $$a=e^x/2$$ and $$b=e^{-x}/2$$ (both of which are clearly positive),

$$\cosh(\cosh x)-\cosh(\sinh x)\gt2\cdot{e^x\over2}\cdot{e^{-x}\over2}={1\over2}$$

as desired.

• On closer inspection, this is essentially the same as user21467's answer, just differently presented. Commented Jun 12, 2021 at 14:33